High prevalence of gastroesophageal reflux symptoms in patients with both acute and nonacute cough - Motohide Iwata; Hiroki Ota; Toshiyasu Watanabe; Yoshihisa Urita; Yosuke Sasaki; et al (International Journal of General Medicine, 2008)
Yoshihisa Urita, Toshiyasu Watanabe, Hiroki Ota, Motohide Iwata, Yosuke Sasaki, et alDepartment of General Medicine and Emergency Care, Toho University School of Medicine, Omori Hospital, Tokyo, JapanAbstract: Although there have been many studies that showed a close association between gastroesophageal reflux disease (GERD) symptoms and chronic cough, it has been unknown whether acute cough is also associated with GERD. The aim of this study was to evaluate the relationship between GERD and respiratory symptoms in general practice. 1725 consecutive patients who first attended our hospital were enrolled in the present study. They were asked to respond the F-scale questionnaire regardless of their chief complaints. Over all, 656 (38%) patients were diagnosed as GERD and 226 (13%) had respiratory symptoms. Patients with respiratory symptoms had GERD symptoms more frequently than patients without respiratory symptoms (p < 0.05). Forty-three (37%) of 115 patients with acute cough and 48 (43%) of 111 with nonacute cough had GERD symptoms, suggesting that development of GERD is not associated with the period of respiratory symptoms. Patients with respiratory symptoms are at a significantly increased risk of developing GERD. Whether or not treatment for GERD or respiratory diseases is useful for the prevention of respiratory symptoms and GERD, respectively, should not be driving management decisions in primary care.Keywords: acute cough, gastroesophageal reflux, chronic cough, F-scale